Understanding Cardiovascular Risk: Insights From Coastal Communities in Southeast Sulawesi - Syahrianti Syahrianti; Lilin Rosyanti; Reni Revianti Usman; Ismail Ismail; Agus Bintara Birawida; Sumarheni Sumarheni; Muhammad Fahmi Aziz (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Cardiovascular Disease (CVD) remains the leading cause of death worldwide, with a greater impact on low- and middle-income countries, particularly coastal communities that depend on fragile ecosystems. This study explores the effects of sociodemographic, behavioral, and metabolic factors on CVD incidence among the coastal population of Soropia, Konawe, Southeast Sulawesi. This research employs a quantitative approach with a cross-sectional design and applies Structural Equation Modeling (SEM) using Smart PLS software. Data collection was conducted through standardized questionnaires and physical examinations. The findings reveal that age significantly reduces CVD risk (p = 0.043, Exp(B) = 0.378), while gender and occupation show no significant impact. Among behavioral factors, a history of Non-Communicable Diseases (NCDs) significantly lowers CVD risk (p = 0.024, Exp(B) = 0.158), whereas smoking, alcohol consumption, and physical activity are not associated with CVD Risk. In the metabolic group, Low-Density Lipoprotein (LDL) is the only significant factor influencing metabolic risk (p = 0.026, Exp(B) = 0.615). Other metabolic markers, including waist circumference and blood glucose, show weak associations. These results highlight the critical role of addressing behavioral and metabolic risk factors in reducing CVD burden, particularly through targeted public health interventions tailored to the unique challenges faced by coastal populations. The study underscores the importance of integrating behavioral modifications and metabolic risk management in health programs to mitigate CVD risks effectively.